PENGARUH PERTUMBUHAN PERUSAHAAN DAN LEVERAGE TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN - SARI, PUTU INDAH PURNAMA; ABUNDANTI, NYOMAN (E-Jurnal Manajemen, 2014)
The aim of this study was to determine the effect of company’s growth, profitability and leverage the value of companies in the sectors of food and beverages companies listed on stock exchanges in Indonesia. Sample size was 33 samples were selected using purposive sampling technique. This study used path analysis techniques. Based on analysis of the company’s growth (growth) positive significant effect on profitability (ROA), growth (growth) positive significant effect on firm value (PBV), leverage (DAR) negative significant effect on profitability (ROA), leverage (DAR) negative significant effect on firm value (PBV), and profitability (ROA) positive significant effect on firm value (PBV). Keywords: growth, leverage, profitability and firm value.